Antinociceptive activity of methanolic extract of Acmella uliginosa (Sw.) Cass - Hui Ming Ong; Azam Shah Mohamad; Nor 'Adilah Makhtar; Mohamed Hanief Khalid; Syamimi Khalid; Enoch Kumar Perimal; Siti Nurulhuda Mastuki; Zainul Amiruddin Zakaria; Nordin Lajis; Daud Ahmad Israf; Mohd Roslan Sulaiman (Elsevier, 2024)
Journal of Ethnopharmacology Volume 133, Issue 1, 7 January 2011, Pages 227-233